Embelin attenuates lipopolysaccharide-induced acute kidney injury through the inhibition of M1 macrophage activation and NF-κB signaling in mice. Issue 3 (March 2023) - Tang, Qiao; Tang, Yun; Yang, Qun; Chen, Rong; Zhang, Hong; Luo, Haojun; Xiao, Qiong; Liu, Kaixiang; Huang, Liming; Chen, Jie; Wang, Lin; Song, Xinrou; et al.
Abstract: Septic acute kidney injury (AKI) is commonly associated with renal dysfunction and high mortality in patients. Owing to the rapid and violent occurrence of septic AKI with inflammation, there are no effective therapies to clinically treat it. Embelin, a natural product, has a potential regulatory role in immunocytes. However, the role and mechanism of embelin in septic AKI remains unknown. This study aimed to elucidate the role of embelin in macrophage regulation in lipopolysaccharide (LPS)-induced septic AKI. Embelin was intraperitoneally administered to mice after LPS injection. And bone marrow-derived macrophages (BMDMs) were subsequently isolated from the mice to explore the immunomodulatory role of embelin in macrophages. We found that embelin attenuated renal dysfunction and pathological renal damage in the LPS-induced sepsis mouse model. Molecular docking predicted that embelin could bind to phosphorylated NF-κB p65 at the ser536 site. Embelin inhibited the translocation of NF-κB p65 via phosphorylation at ser536 in LPS-induced AKI. It also reduced the secretion of IL-1β and IL-6 and increased the secretion of IL-10 and Arg-1 of BMDMs and mice after LPS stimulation, indicating that embelin suppressed macrophage M1 activation in LPS-induced AKI. Therefore, embelin attenuated LPS-induced septic AKI by suppressing NF-κB p65 at ser536 in activated macrophages. This study preclinically suggests a therapeutic role of embelin in septic AKI.